Kualitas Layanan Perpustakaan Kota Magelang Berdasarkan Dimensi LibQUAL+TM pada Persepsi Generasi Muda - Kayla Chintya Lee Rahman; Abhinaya Hafidzhah Liu; Gladys Kirani Adittya; Marsya Mutiara Syalwa; Bayu Mufa’uzun; Joko Tri Nugraha (ANTASENA: Governance and Innovation Journal, 2026)
The purpose of this study is to assess the quality of services at the Magelang City Library from the perspective of the younger generation through the application of the LibQUAL+TM approach. The primary focus of this study is to determine how users aged 15 to 24 perceive the quality of library services, which includes aspects such as the Service Affect, the Library as Place, Personal Control, and Informaation Access. To determine respondents who met the study criteria, a descriptive quantitative method using simple random sampling was employed. To measure user satisfaction with library services, a questionnaire was distributed to 110 individuals out of a total of 20,074 users, with a margin of error of 10%. The Likert scale ranged from 1 to 5. The research results indicate that the overall quality of services at the Magelang City Library is considered satisfactory. Library as Place received the highest score because the library’s physical facilities were rated as comfortable, clean, and pleasant, and were able to support reading and learning activities for the younger generation. Additionally, the Service Affect aspect was also rated positively because librarians were perceived as friendly, responsive, communicative, and capable of effectively meeting visitors’ needs. However, the aspects of Personal Control and Information Access continued to show a significant neutral response. Therefore, in the future, libraries must focus on developing digital services, improving the quality of their information collections, providing more modern facilities, and optimizing their information retrieval systems.